2020
DOI: 10.1183/23120541.00237-2020
|View full text |Cite
|
Sign up to set email alerts
|

The association of pulmonary fibrosis with diabetes mellitus

Abstract: Idiopathic pulmonary fibrosis (IPF) is the most studied fibrotic lung disease and has overlapping pathogenesis with other fibrotic lung diseases. It is associated with a high prevalence of other comorbidities, such as COPD, lung cancer and coronary artery disease, due to common risk factors such as smoking and older age [1]. Several case–control studies have also suggested a link between IPF and diabetes mellitus. These studies have reported a higher prevalence of diabetes in IPF patients compared to matched c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Those less than 45 years old were excluded as the diagnosis of IPF and LC were rare in this age group. In comparing those with and without IPF, logistic regression was utilized to obtain the adjusted odds ratio (OR) as in prior studies [5]. To analyze the temporal trends, Poisson regression modeling was used (negative binomial regression was used for overdispersed data).…”
Section: Methodsmentioning
confidence: 99%
“…Those less than 45 years old were excluded as the diagnosis of IPF and LC were rare in this age group. In comparing those with and without IPF, logistic regression was utilized to obtain the adjusted odds ratio (OR) as in prior studies [5]. To analyze the temporal trends, Poisson regression modeling was used (negative binomial regression was used for overdispersed data).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown the incidence of ARDS to be lower among diabetics, and it is possible that diabetes may similarly reduce the risk of AE-IPF [25,26]. The prevalence of pulmonary fibrosis has also been noted to be lower in diabetic decedents compared to non-diabetic decedents in a large population-based study [27]. Yet the previous literature does not suggest a relationship between diabetes and ARDS mortality [28,29].…”
Section: Comparison With Previously Published Datamentioning
confidence: 99%
“…Diabetes is a comorbidity in IPF and its prevalence in IPF patients appears to depend also on ethnicity [ 13 , 17 ]. Diabetes prevalence in Danish IPF patients in a cohort study between 2003 and 2009 showed that at the beginning of the study there were 9% patients with diabetes and an additional 8% of the patients were diagnosed with diabetes during the follow-up of the study; thus a total of 17% of patients with IPF had also diabetes.…”
Section: Pulmonary Fibrosis Comorbiditiesmentioning
confidence: 99%
“…The presence of diabetes at the beginning of the study was associated with higher IPF mortality compared to those who did not have diabetes at the beginning of the study [ 13 ]. In the US, a retrospective population-based study using CDC database from 2007 to 2017 identified IPF in 0.65% of diabetic patients and 0.80% in non-diabetic patients [ 17 ]. Most body organ functions such as those of kidneys, retina, heart, brain, and lungs are profoundly affected by diabetes [ 18 ].…”
Section: Pulmonary Fibrosis Comorbiditiesmentioning
confidence: 99%